2007
DOI: 10.3900/fpj.6.6.357.e
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between quality of life and physical activity in college students attending a physical education course

Abstract: Introduction: The present study aimed to identify the relationship between quality of life (QL) and physical activity (PA) in college students attending a Physical Education Course. Materials and Methods: The research had a traverse and descriptive method, with 85 college students (46 male and 39 female) from Ponta Grossa -PR municipal district. The level of PA (physical activity) by IPAQ (brief version) and QL were measured applying the WHOQOL-Bref. To verify association between sex and PA the test quisquare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…The data on low frequency compared to the practice of physical activity are consistent with studies with Physical Education professionals, where the practice of exercise was positively associated with perception of high quality of life in men [38].…”
Section: Physical Activitysupporting
confidence: 85%
See 1 more Smart Citation
“…The data on low frequency compared to the practice of physical activity are consistent with studies with Physical Education professionals, where the practice of exercise was positively associated with perception of high quality of life in men [38].…”
Section: Physical Activitysupporting
confidence: 85%
“…Likewise, there are the psychological factors such as behavior, which is a necessary link in the chain that causes most of the environmental and genetically determinants having consequent effects in health [12]. There have been different investigators who have reported the influence of lifestyles as protective factors either as risk factors for the existence of the health status or the presence of the disease in the population [13][14][15][16][17]. Furthermore, significant associations have been found in the lifestyle of the health promoter, with the different psychosocial variables such as: perception in the context's problems, satisfaction concerning different aspects of life, affective support and trust; self-esteem and self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…From the standpoint of the participants' sex, men reported higher levels of quality of life in all the domains than women. In a study involving physical education students, Cieslak [24] found a statistical difference only in the domain of "social relations," in which women presented the higher average. Male nursing students showed statistically higher averages in the "physical" and "psychological" domains [16].…”
Section: Discussionmentioning
confidence: 97%
“…Among university students, this score was higher in studies involving psychology students in Rio Grandedo Sul 71.3% [18]; Physical Education students in Paraná 70.9% [24]; and nursing students in Santa Catarina 64% [20], and lower than the study involving young athletes in Paraná 73% [25].…”
Section: Discussionmentioning
confidence: 99%
“…Revista de Psicología de la Salud (New Age) Vol 5, nº1, 2017 en segundo lugar los españoles y finalmente los mexicanos. Mientras que en la situación económica, los catalanes se ubicaron en último lugar en cuanto a la media de satisfacción, en segundo los coahuilenses y en primero los estudiantes de Nuevo México.En el nivel de satisfacción general de la vida, los estadounidenses obtuvieron la media más alta, en segundo lugar los catalanes y finalmente los coahuilenses, aunque de manera general reportaron un nivel de satisfacción alto.DISCUSIÓN.De manera general, los estudiantes universitarios de los tres países poseen un alto nivel de satisfacción general de sus vidas, lo cual podemos entender como un reflejo de su etapa de desarrollo, nivel de escolaridad(Herrera et al, 2015), así como las interacciones positivas, las cuales son un medio de salud y recreación, y que además tienen que ver con las habilidades sociales que permiten una adaptación eficaz y efectiva a las áreas de su vida (Urdaneta & Morales, 2013), áreas en la que los estudiantes se reportaron satisfechos; coincidiendo con otros estudios con poblaciones similares(Vargas, 2006; Vera, Laborín, Córdova, & Parra, 2007: Cieslak et al, 2007.Por otro lado, la salud es uno de los aspectos principales como reguladora de la percepción de la calidad de vida; y en esta área, los…”
unclassified